2009
DOI: 10.1021/ef800976y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fuel Type and Deposition Surface Temperature on the Growth and Structure of an Ash Deposit Collected during Co-firing of Coal with Sewage Sludge and Sawdust

Abstract: Blends of a South African bituminous "Middleburg" coal, a municipal sewage sludge, and a sawdust have been fired in the slagging reactor to examine the effect of the added fuel on the slagging propensity of the mixtures. Two kinds of deposition probes have been used, uncooled ceramic probes and air-cooled metal probes, to examine the influence of the deposition surface temperature on both the deposit growth and its structure. The initial stages of slagging (140 min of sampling) have been investigated in two te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…This does not greatly change the geometry of the deposit surface and affect the particle impaction and deposition behaviour. Kupka et al [34] experimentally found a linear ash deposition rate in the early stage, which also supports the 'steady state' assumption in this study.…”
Section: Case Set-up and Uncertainty Analysissupporting
confidence: 91%
“…This does not greatly change the geometry of the deposit surface and affect the particle impaction and deposition behaviour. Kupka et al [34] experimentally found a linear ash deposition rate in the early stage, which also supports the 'steady state' assumption in this study.…”
Section: Case Set-up and Uncertainty Analysissupporting
confidence: 91%
“…Figure 4 shows a typical diagram of process temperature-base-acid ratio, as an indi-cator of slagging/fouling for the cofiring of Kakanj brown coal with spruce sawdust. This corresponds to the explanation given by Raask [11]. Above this temperature, ash deposition of the coal-sawdust mixtures was accentuated; ash deposits were melted and then hardened.…”
Section: Investigated Of Slagging and Fouling-related Problems On Labsupporting
confidence: 85%
“…They do not represent a threat to the stability of operation or the efficiency of the boiler. Only slight change in NO x emissions can be noticed with the change of fuel, and there is no clear correlation between the influence of adding biomass to the emission of NO x , which is consistent with experimental research described above, as well as with many findings in the world on the phenomenon of the influence of biomass on emissions of NO x , see [9][10][11]. The base-acid ratio for the ash deposits is given in fig.…”
Section: Slagging/fouling Assessment Based On the Trial Runsupporting
confidence: 83%
“…Zhou et al [5,6] used a digital imaging system protected by cooling water and compressed air to monitor the growth of ash deposition. Additionally, surface temperature plays an important role in ash deposition [7][8][9][10]. Zhou et al [11] found that the temperature of the deposition surface had a significant effect on the deposition rate and morphology, and that the deposition thickness increased as the surface temperature decreased.…”
Section: Introductionmentioning
confidence: 99%